If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3x = x Combine like terms: 6x + 3x = 9x 9x = x Solving 9x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9x + -1x = x + -1x Combine like terms: 9x + -1x = 8x 8x = x + -1x Combine like terms: x + -1x = 0 8x = 0 Divide each side by '8'. x = 0 Simplifying x = 0
| 120=x(x-14) | | 3x/5=-15 | | 5y^2-7xy-6x^2=0 | | s=4n+4u | | x^2+4x+x+4= | | 6y+2y=24 | | x/-4=14 | | X/5+7=16 | | 3(2x+4)=45 | | 9/3-(5/a) | | 10x+10=15x+6 | | 4+15t-2=7t+41-5t | | X(x-14)=120 | | 54.5=15x-73 | | 40+14j=-8j-13 | | -2/3(-2x+7)=-6 | | 3y^2-108= | | 36x-6x^2=0 | | -3(-x)=0 | | 2-4(2-5x)=0 | | 7+Log[3](5x)=9 | | 18x^2-2x^3=0 | | -2/3(c+6)=2(c/3+3) | | (15w^2-6w)= | | m+-5=2 | | x/4+3x/1=26 | | m+31=17 | | 2s+2s=28 | | X/4+3x/1 | | 5/6(-5x+2)=8 | | 2g+7g=-4g+7+6g | | 2(2x-5)=7+6x |